Corrosion of indium doped E-AlMgSi aluminum conductor alloy (Aldrey) - Izatullo N. Ganiev (Pensoft Publishers, 2021)
The effect of impurities on the electrical conductivity of aluminum has been studied in detail. The electrical conductivity of aluminum is 65.45% of that of copper. The tensile strength of aluminum wire is 150–170 MPa which, at equal conductivity, is about 65% of the strength of copper wire. This strength of aluminum wire is sufficient for bearing the wire’s own weight but may be too low in case of snow, ice or wind overloads. One way to improve the strength of aluminum wire is to use aluminum alloys having higher strength combined with sufficiently high electrical conductivity, e.g. the E-AlMgSi alloy (Aldrey). The key strengthening agent of the E-AlMgSi alloy (Aldrey) is the Mg2Si phase which imparts high mechanical strength to aluminum. In this work we present experimental data on the kinetics of high-temperature oxidation and electrochemical corrosion of indium doped E-AlMgSi aluminum conductor alloy (Aldrey). Thermal gravimetric study has shown that indium doping and high temperature exposure increase the oxidation rate of E-AlMgSi alloy (Aldrey), with the apparent alloy oxidation activation energy decreasing from 120.5 to 91.8 kJ/mole. Alloy oxidation rate data determined using a potentiostatic technique in NaCl electrolyte media have shown that the corrosion resistance of the indium doped alloy is 20–30% superior to that of the initial alloy. With an increase in NaCl electrolyte concentration the electrochemical potentials of the alloys decrease whereas the corrosion rate increases regardless of alloy composition.